1998
DOI: 10.1103/physrevlett.81.409
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Dendritic Array Stability

Abstract: Stability of a uniformly spaced dendritic array against a spatial period doubling instability was studied through UV thermal perturbations of every other dendrite tip. We observed that above a critical pulling speed the array is stable against these perturbations and we measured decreasing decay rates of the perturbed mode as we approached the critical speed. In the linear regime, our measurements are qualitatively consistent with the Warren-Langer linear stability analysis for a dendritic array [J. A. Warren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Hence, investigations of the primary spacing evolution from the initial planar instability during directional solidification are very important for the determination of the final mean primary spacing. Experiments [7,8] and simulations [28][29][30] for the planar instability and subsequent spacing adjustment have been carried out. However, few quantitative investigations have been devoted to the tilted growth of dendritic arrays.…”
Section: Primary Spacing and Growth Direction Selection From Initial mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, investigations of the primary spacing evolution from the initial planar instability during directional solidification are very important for the determination of the final mean primary spacing. Experiments [7,8] and simulations [28][29][30] for the planar instability and subsequent spacing adjustment have been carried out. However, few quantitative investigations have been devoted to the tilted growth of dendritic arrays.…”
Section: Primary Spacing and Growth Direction Selection From Initial mentioning
confidence: 99%
“…Previous theoretical [4,5], experimental [6][7][8], and numerical [9,10] investigations have shown that a wide range of primary spacing can be selected for the same control parameters in directional solidification. Beyond this range of primary spacing, there is an abrupt transition to a new stable array due to the spacing adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…The necessary perturbation strength can be quantified from the response to small perturbations [11]. Here a 0 and a 1 are linear and third order growth coefficients, respectively.…”
Section: Article In Pressmentioning
confidence: 99%
“…6,7 In the current understanding of the problem, this transient determines the result of the selection process. 4,5 Indeed, calculations performed by using the instability of the steady state are known to yield wrong results on the selected wavelength when comparing to experiments. 8,9 While thermal and concentration gradients can induce convection in the melt, this effect has received little attention in time-dependent solidification problems, but it has nevertheless been studied by using different approximations in some solidification setups.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, in dendritic growth, solutions with different wavelengths are possible for a given growth condition, 3 and the final one is dynamically selected during the initial transient states of the solidification process. 4,5 The fact is that after setting the final value of the pulling velocity, there is a transient in which a layer of solute is built up ahead of the advancing front, during which the instability can occur. 6,7 In the current understanding of the problem, this transient determines the result of the selection process.…”
Section: Introductionmentioning
confidence: 99%